A comparison of stress hormone concentrations at slaughter in Nguni, Bonsmara and Angus steers - Thulile Ndlovu; Michael Chimonyo; Anthony I. Okoh; Voster Muchenje (Global Journal of Plant and Soil Sciences, 2020)
Concentrations of stress hormones at slaughter were determined in 15 of each of 18-month old Angus, Bonsmara and Nguni steers. The steers were slaughtered at the East London Abattoir, which is about 120 km from the University of Fort Hare farm, where the animals had been raised. Serum creatinine and packed cell volume (PCV) concentrations were determined before cattle transportation. Blood was also collected along the slaughter line immediately after exsanguination for the determination of cortisol, creatinine and PCV. Urine samples were collected for the measurement of creatinine, adrenaline, noradrenaline and dopamine concentrations. Estimated glomerular filtration rate was also determined. Bonsmara had the highest concentrations of adrenaline (10.8 nmol/mol), noradrenaline (9.7 nmol/mol) and dopamine (14.8 nmol/mol) concentrations, whereas the Nguni had the least concentrations of adrenaline (6.5 nmol/mol), noradrenaline (4.6 nmol/mol) and dopamine (4 nmol/mol) concentrations. The Nguni had the highest serum cortisol concentrations (2.3 nmol/mol), while Angus had the least concentrations (1.3 nmol/mol). There were no (P > 0.05) breed differences in serum and urea creatinine concentrations, and on estimated glomerular filtration rate (eGFR). Bonsmara steers had higher (P < 0.05) levels of catecholamines and dopamine compared to Nguni and Angus steers after transport and handling stress. The Bonsmara was therefore the most stress responsive breed at slaughter.